Preparation process of electromagnetic radiation-proof polymer sound insulation material for new energy cars
By using modified hollow glass microbeads, modified mica powder and modified calcium carbonate in anti-electromagnetic radiation polymer sound insulation materials for new energy vehicles, the problem of poor compatibility of existing water-based damping coatings is solved, and efficient damping and electromagnetic shielding effects are achieved.
Patent Information
- Application Number
- CN202411173709.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing water-based damping coatings have poor compatibility with the resin matrix and are difficult to disperse evenly in the coating, resulting in a reduced damping and sound insulation performance.
The damping filler is prepared by using synthetic emulsions, modified hollow glass microbeads, modified mica powder and modified calcium carbonate through multiple steps such as coarseness, sensitization, activation and silver plating, and is uniformly dispersed in the synthetic emulsion matrix to form a polymer sound insulation material.
It improves the damping performance and electromagnetic shielding performance of the material, widens the effective damping temperature range, and enhances the adhesion and impact resistance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sound insulation materials, and in particular to a preparation process of an electromagnetic radiation proof polymer sound insulation material for new energy cars. Background Art
[0002] With the rapid development of the automobile industry and the continuous improvement of various supporting facilities, people are paying more attention to the comfort of automobiles while paying attention to the performance of automobiles. They are paying more and more attention to the control of vehicle body vibration and noise inside the car. The control of the level of noise inside the car has gradually become one of the important indicators for measuring the quality of passenger cars. In the field of automobile noise and vibration, the riding comfort performance of the car is usually characterized by studying the NVH of the car. NVH is the abbreviation of Noise, Harshness and Vibration. The noise and vibration generated by the car when driving mainly come from the following five aspects: tires, suspension system, body, wind resistance and engine. In summary, the noise inside the car mainly comes from the noise generated during air intake and exhaust, the noise generated by body radiation, the noise generated by the chassis and the noise generated when the engine is working. There are two ways to transmit noise: (1) through the structure; (2) through the air. Moreover, through surface research, it is generally found that the structural vibration mainly transmits the medium and low frequency (30Hz-400Hz) noise inside the car, while other high frequency noise is transmitted to the interior of the car through the gaps and holes in the body through the air.
[0003] The car body is composed of many complex thin-walled panels, which leads to the complexity of the car body structure. In addition, the car body is not only subject to vibration excitation caused by the transmission of the powertrain, but also random excitation caused by uneven roads, and even transmission system excitation and wind excitation. In order to reduce noise and vibration, damping materials are generally used. The resistance material can convert sound energy and vibration energy into heat and dissipate it. Due to the disadvantages of traditional damping materials, high-performance and environmentally friendly liquid sprayable damping materials have emerged. Water-based damping coatings are prepared with resin as the matrix, water as the dispersant, and a large amount of inorganic materials such as mica powder and calcium carbonate with a lamellar structure. Spraying the damping coating on the vibrating component shell can suppress the vibration of the shell and reduce noise. However, due to the different surface properties of inorganic fillers and resin matrix, the compatibility between the two is poor, and it is difficult to disperse evenly in the coating, which greatly reduces the damping and sound insulation performance of the coating. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of an electromagnetic radiation-proof polymer sound insulation material for new energy cars to solve the following technical problems:
[0005] Existing water-based damping coatings are made of resin as the matrix, water as the dispersant, and a large amount of inorganic substances such as mica powder and calcium carbonate with a lamellar structure. Due to the different surface properties of the inorganic filler and the resin matrix, the two have poor compatibility and are difficult to disperse evenly in the coating, which greatly reduces the damping and sound insulation performance of the coating.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A preparation process of an electromagnetic radiation-proof polymer sound insulation material for new energy cars comprises the following steps:
[0008] According to the raw material ratio, the synthetic emulsion, damping filler, dispersant, defoamer and plasticizer are evenly dispersed, and water and thickener are added to adjust the viscosity of the system to obtain an electromagnetic radiation protection polymer sound insulation material;
[0009] The preparation method of the damping filler comprises the following steps:
[0010] S1: Add silver-plated hollow glass microspheres, p-mercaptoaniline and anhydrous ethanol into reactor A and disperse them evenly, let them stand at room temperature for 24-36 hours, wash with water and dry them to obtain organic hollow glass microspheres;
[0011] S2: adding the organic hollow glass microspheres, isopropanol and deionized water into the reaction kettle B and dispersing them evenly, blending aniline and hydrochloric acid solution and adding them into the reaction kettle, stirring at room temperature for 0.5-1h, adding ammonium persulfate, controlling the temperature at -5 to 5°C, keeping the temperature under stirring for 3-6h, washing, filtering and drying to obtain modified hollow glass microspheres;
[0012] S3: Blending the modified hollow glass microspheres, silane-modified mica powder and silane-modified calcium carbonate to obtain a damping filler.
[0013] As a further solution of the present invention: the addition ratio of the silver-plated hollow glass microspheres, p-mercaptoaniline and anhydrous ethanol in S1 is 10 g: 1-4 g: 100-500 mL.
[0014] As a further solution of the present invention: the hydrochloric acid solution in S2 is a 1-2.5 mol / L hydrochloric acid solution; the addition ratio of the organic hollow glass microspheres, isopropanol, deionized water, aniline, hydrochloric acid solution, and ammonium persulfate is 10 g: 50-100 mL: 200-300 mL: 3-3.5 g: 300-400 mL: 5-8 g.
[0015] As a further solution of the present invention: the mass ratio of the modified hollow glass microspheres, the silane-modified mica powder and the silane-modified calcium carbonate in S3 is 15-20:10-15:10.
[0016] As a further solution of the present invention: the preparation method of silver-plated hollow glass microspheres comprises the following steps:
[0017] (1) Roughening treatment: 3 g of hollow glass microspheres were placed in 200 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate), mechanically stirred for 10 min, and then washed with water;
[0018] (2) Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitizing solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before being washed with water;
[0019] (3) Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0020] (4) Silver plating treatment: The sensitized hollow glass microspheres were placed in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) and treated at 30°C for 40 min to obtain silver-plated hollow glass microspheres.
[0021] As a further scheme of the present invention: a method for preparing γ-methacryloxypropyltrimethoxysilane modified mica powder comprises the following steps: adding anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane into a reaction kettle and dispersing them evenly, adding glacial acetic acid to adjust the pH to 4-5, adding mica components and dispersing them evenly, controlling the temperature at 100-110° C., keeping the temperature for 0.5-1 h, filtering and drying to obtain γ-methacryloxypropyltrimethoxysilane modified mica powder.
[0022] As a further solution of the present invention: the mica component is obtained by mixing mica powders with particle sizes of 38 um, 75 um, 19 um and 0.1 um in a mass ratio of 1:1:1:1.
[0023] As a further solution of the present invention: the addition ratio of anhydrous ethanol, γ-methacryloxypropyltrimethoxysilane and mica component is 20-50mL: 2-5g: 10g.
[0024] As a further scheme of the present invention: a preparation method of γ-methacryloxypropyltrimethoxysilane modified calcium carbonate comprises the following steps: adding γ-methacryloxypropyltrimethoxysilane and anhydrous ethanol component one into a reaction kettle and dispersing them evenly, adding glacial acetic acid to adjust the pH to 4-5, blending calcium carbonate (particle size of 18um) and anhydrous ethanol component two and then adding them into the reaction kettle, controlling the temperature at 60-70°C, keeping the temperature for 2-4h, filtering, washing and drying to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate.
[0025] As a further solution of the present invention: the addition ratio of γ-methacryloxypropyltrimethoxysilane, anhydrous ethanol component one, calcium carbonate, and anhydrous ethanol component two is 5-7g:20-30mL:100g:1000-1200mL.
[0026] As a further solution of the present invention: the dispersant is one of dispersant BYK190, dispersant BYK194N, dispersant BYK2015, dispersant TEGO747W, dispersant TEGO760W, or a mixture of any of them in any ratio.
[0027] As a further solution of the present invention: the defoamer is one of defoamer DF-851, defoamer DF-8202, defoamer DF-8205, and defoamer DF-8206, or a mixture of any of them in any ratio.
[0028] As a further solution of the present invention: the plasticizer is one of diisononyl phthalate, diisodecyl phthalate, and dipropylene glycol diformate, or a mixture of any of them in any ratio.
[0029] As a further embodiment of the present invention, the thickener is any one of VA-2 series acrylic thickener, VA-3 series acrylic thickener or polyurethane thickener.
[0030] As a further solution of the present invention: the electromagnetic radiation protection polymer sound insulation material includes the following raw materials in weight percentage: 45-55% synthetic emulsion, 30-45% damping filler, 1-5% water, 0.3-1.5% dispersant, 0.1-0.3% defoaming agent, 0.1-1% plasticizer, 0.2-1% thickener, and the sum of the weight percentages of each raw material is 100%.
[0031] As a further embodiment of the present invention: the preparation method of the synthetic emulsion comprises the following steps:
[0032] A1: In a nitrogen atmosphere, add deionized water, emulsifier, and acrylic ester monomer into reaction bottle A and disperse evenly, stir for 0.5-1h, control the temperature at 70-90°C, add ammonium persulfate component 1 and sodium bicarbonate, keep warm until blue light appears, keep warm for 0.5-1h, add ammonium persulfate component 2 for post-elimination, adjust the pH to 8-9, filter, and obtain a water-based acrylic emulsion;
[0033] A2: Add polyvinyl alcohol and aqueous acrylic emulsion into reaction bottle B and disperse them evenly to obtain a synthetic emulsion.
[0034] As a further solution of the present invention: the ammonium persulfate component 1 and the ammonium persulfate component 2 in A1 are both ammonium persulfate, the mass ratio of the ammonium persulfate component 1 to the ammonium persulfate component 2 is 1:2-1:3, and the ammonium persulfate accounts for 0.3-0.4% of the total mass of the aqueous acrylic emulsion.
[0035] As a further solution of the present invention: the emulsifier is a mixture of sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether in a mass ratio of 1:1-2; the emulsifier accounts for 2-3% of the total mass of the aqueous acrylic emulsion.
[0036] As a further solution of the present invention: the acrylic acid ester monomer is obtained by mixing styrene, butyl acrylate and methyl methacrylate in a mass ratio of 20-24:22-24:10, and the monomer accounts for 30-33% of the total mass of the aqueous acrylic emulsion.
[0037] As a further embodiment of the present invention, sodium bicarbonate accounts for 0.5-0.8% of the total mass of the aqueous acrylic emulsion.
[0038] As a further solution of the present invention: the mass ratio of polyvinyl alcohol to aqueous acrylic emulsion in A2 is 1:1-2.
[0039] Beneficial effects of the present invention:
[0040] (1) The present application uses the prepared synthetic emulsion as a base material, organically modified mica powder, lamellar structures such as heavy calcium carbonate, and modified hollow glass microspheres as damping fillers, and adds thickeners and other coating additives to obtain an electromagnetic radiation-proof polymer sound insulation material for new energy cars through high-speed stirring.
[0041] The present application first uses a variety of olefinic substances containing unsaturated double bonds as monomer raw materials, uses ammonium persulfate as an initiator, and sodium bicarbonate as a buffer, and undergoes a free radical polymerization reaction to obtain an aqueous acrylic emulsion; and uses the aqueous acrylic emulsion and polyvinyl alcohol to prepare a synthetic emulsion with an interpenetrating network structure. The present application utilizes an intermediate structure between the two networks of the polymer to achieve a forced compatibility state between the two networks, effectively fills the trough between the Tg peaks of the two resins, improves the damping performance, and achieves the effect of widening the effective damping temperature range.
[0042] (2) The present application prepares damping fillers by blending modified hollow glass microspheres, modified mica powder and modified calcium carbonate; the present application uniformly disperses the modified silver-plated hollow glass microspheres, modified mica powder and modified calcium carbonate in a synthetic emulsion matrix. The viscoelasticity of the polymer material converts the energy of mechanical vibration and acoustic vibration into heat energy or other dissipative energy. The hollow structure of the hollow glass microspheres, the layered structure of the mica powder and the calcium carbonate constitute the sound-absorbing material, which allows most of the sound waves to enter the material. The sound waves are gradually consumed during the propagation process, giving the material damping properties. Mica powder has a lamellar structure and a large specific surface area. It increases the contact area between the filler and the emulsion in the coating. When external vibration occurs, directional sliding occurs, increasing the frictional internal loss of the coating. At the same time, adding mica powder of different particle sizes can increase the surface density of the coating and increase the attenuation of sound waves. When the coating dries and forms a film, the calcium carbonate powder plays a good role in attenuating sound waves and exhibits good sound insulation performance in the medium and low frequency range.
[0043] The present application simultaneously utilizes γ-methacryloxypropyltrimethoxysilane to organically modify calcium carbonate and mica powder, and the hydrolyzed silanol groups undergo dehydration condensation with the hydroxyl groups on the surfaces of calcium carbonate and mica powder to organically modify the surfaces of nanoparticles, and the modified surfaces of calcium carbonate and mica powder are grafted with double bonds, and the organic siloxane molecular chains on the surfaces of calcium carbonate and mica powder participate in the polymerization reaction of acrylic resin, and Si-O bonds are introduced into the molecular chains of acrylic resin, so that a -Si-O-Si- stereo cross-linked network is formed between the emulsions, and the entanglement between bonds is enhanced, which not only gives the coating film better ductility; but also there is a strong interaction between the nanoparticles and the polymer, which hinders the movement of the polymer chain, increases the internal friction resistance, and widens the damping temperature, so that the obtained coating has the characteristics of high damping and a wide temperature range.
[0044] (3) The present application firstly roughens, sensitizes and activates hollow glass microspheres to obtain pretreated hollow glass microspheres; then silver-plates the surface of the pretreated hollow glass microspheres to obtain silver-plated hollow glass microspheres; then the mercapto group of para-mercaptoaniline reacts with the silver layer on the surface of the silver-plated hollow glass microspheres to form a strong Ag-S chemical bond to obtain organic hollow glass microspheres; finally, the aniline on the surface of the organic hollow glass microspheres is used as a bridge to organically combine polyaniline with the hollow glass microspheres to obtain modified hollow glass microspheres; finally, the modified hollow glass microspheres, silane-modified mica powder and silane-modified calcium carbonate are blended to obtain damping filler.
[0045] The present application performs organic treatment on the surface of the silver-plated hollow glass microspheres, which not only increases the interface of the composite material, resulting in multiple reflections of electromagnetic waves inside the material and improving the electromagnetic shielding performance of the material, but also the polyaniline resin layer coated on the surface of the silver-plated hollow glass microspheres effectively blocks the direct contact between the silver layer and the substrate and the outside world, maintains the integrity of the silver layer and the conductive network in the use environment of stretching, bending, folding, etc., and further gives the material good electromagnetic shielding performance. DETAILED DESCRIPTION
[0046] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0047] The preparation method of the synthetic emulsion comprises the following steps:
[0048] A1: In a nitrogen atmosphere, 64 g of deionized water, 1 g of sodium dodecylbenzene sulfonate, 1 g of nonylphenol polyoxyethylene ether, 13.2 g of styrene, 13.8 g of butyl acrylate, and 6 g of methyl methacrylate were added to reaction bottle A and dispersed evenly, stirred for 0.5-1 h, the temperature was controlled at 70 ° C, 0.1 g of ammonium persulfate and 0.6 g of sodium bicarbonate were added, and the reaction was kept warm until blue light appeared, and the heat was kept warm for 1 h, 0.3 g of ammonium persulfate was added for post-elimination, ammonia water was added to adjust the pH to 8, and filtered to obtain a water-based acrylic emulsion;
[0049] A2: Add 50g polyvinyl alcohol (PVA1799) and 100g aqueous acrylic emulsion into reaction bottle B and disperse them evenly to obtain a synthetic emulsion. Example 2
[0050] The preparation method of the damping filler comprises the following steps:
[0051] S1: 5 g of mica powder with a particle size of 38 um, 5 g of mica powder with a particle size of 75 um, 5 g of mica powder with a particle size of 19 um, and 5 g of mica powder with a particle size of 0.1 um are mixed to obtain a mica component; 100 mL of anhydrous ethanol and 4 g of γ-methacryloxypropyltrimethoxysilane are added to a reaction kettle and dispersed evenly, glacial acetic acid is added to adjust the pH to 4, 20 g of the mica component is added and dispersed evenly, the temperature is controlled at 100° C., the temperature is kept for 0.5 h, filtered, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder;
[0052] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0053] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0054] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0055] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0056] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min and then washed with water;
[0057] S34: Silver plating treatment: placing the hollow glass microbeads after sensitization treatment in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) at 30°C for 40 min to obtain silver-plated hollow glass microbeads;
[0058] S35: 10 g of silver-plated hollow glass microspheres, 1 g of p-mercaptoaniline, and 100 mL of anhydrous ethanol were added to the reaction kettle A and dispersed evenly, and allowed to stand at room temperature for 246 h, washed with water, and dried to obtain organic hollow glass microspheres;
[0059] S36: 10 g of organic hollow glass microspheres, 50 mL of isopropanol, and 200 mL of deionized water were added to reactor B and dispersed evenly, 3 g of aniline and 300 mL of 2 mol / L hydrochloric acid solution were mixed and added to the reactor, stirred at room temperature for 0.5 h, 5 g of ammonium persulfate was added, the temperature was controlled at -5 °C, and the reaction was kept warm for 3 h under stirring, washed, filtered, and dried to obtain modified hollow glass microspheres;
[0060] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler. Example 3
[0061] The preparation method of the damping filler comprises the following steps:
[0062] S1: 5 g of mica powder with a particle size of 38 um, 5 g of mica powder with a particle size of 75 um, 5 g of mica powder with a particle size of 19 um, and 5 g of mica powder with a particle size of 0.1 um are mixed to obtain a mica component; 100 mL of anhydrous ethanol and 4 g of γ-methacryloxypropyltrimethoxysilane are added to a reaction kettle and dispersed evenly, glacial acetic acid is added to adjust the pH to 4, 20 g of the mica component is added and dispersed evenly, the temperature is controlled at 100° C., the temperature is kept for 0.5 h, filtered, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder;
[0063] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0064] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0065] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0066] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0067] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min and then washed with water;
[0068] S34: Silver plating treatment: placing the hollow glass microbeads after sensitization treatment in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) at 30°C for 40 min to obtain silver-plated hollow glass microbeads;
[0069] S35: 10 g of silver-plated hollow glass microspheres, 2.5 g of p-mercaptoaniline, and 300 mL of anhydrous ethanol were added to the reaction kettle A and dispersed evenly, and allowed to stand at room temperature for 30 h, and then washed with water and dried to obtain organic hollow glass microspheres;
[0070] S36: 10 g of organic hollow glass microspheres, 70 mL of isopropanol, and 250 mL of deionized water were added to reactor B and dispersed evenly, 3.2 g of aniline and 350 mL of 2 mol / L hydrochloric acid solution were mixed and added to the reactor, stirred at room temperature for 0.5 h, 6 g of ammonium persulfate was added, the temperature was controlled at 0°C, the reaction was kept warm for 4 h under stirring conditions, washed, filtered, and dried to obtain modified hollow glass microspheres;
[0071] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler. Example 4
[0072] The preparation method of the damping filler comprises the following steps:
[0073] S1: 5 g of mica powder with a particle size of 38 um, 5 g of mica powder with a particle size of 75 um, 5 g of mica powder with a particle size of 19 um, and 5 g of mica powder with a particle size of 0.1 um are mixed to obtain a mica component; 100 mL of anhydrous ethanol and 4 g of γ-methacryloxypropyltrimethoxysilane are added to a reaction kettle and dispersed evenly, glacial acetic acid is added to adjust the pH to 4, 20 g of the mica component is added and dispersed evenly, the temperature is controlled at 100° C., the temperature is kept for 0.5 h, filtered, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder;
[0074] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0075] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0076] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0077] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0078] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min and then washed with water;
[0079] S34: Silver plating treatment: placing the hollow glass microbeads after sensitization treatment in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) at 30°C for 40 min to obtain silver-plated hollow glass microbeads;
[0080] S35: 10 g of silver-plated hollow glass microspheres, 4 g of p-mercaptoaniline, and 500 mL of anhydrous ethanol were added to the reaction kettle A and dispersed evenly, and allowed to stand at room temperature for 36 h, and then washed with water and dried to obtain organic hollow glass microspheres;
[0081] S36: 10 g of organic hollow glass microspheres, 100 mL of isopropanol, and 300 mL of deionized water were added to reactor B and dispersed evenly, 3.5 g of aniline and 400 mL of 2 mol / L hydrochloric acid solution were mixed and added to the reactor, stirred at room temperature for 1 h, 8 g of ammonium persulfate was added, the temperature was controlled at 5°C, and the reaction was kept warm for 6 h under stirring, washed, filtered, and dried to obtain modified hollow glass microspheres;
[0082] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler. Example 5
[0083] A preparation process of an electromagnetic radiation protection polymer sound insulation material for new energy cars comprises the following steps: 55g of the synthetic emulsion prepared in Example 1, 38g of the damping filler prepared in Example 2, 1g of a dispersant, 0.3g of a defoaming agent DF-851, and 0.5g of diisononyl phthalate are stirred at 400r / min for 60min, 5g of water and 0.2g of a VA-2 series acrylic thickener are added, and the stirring speed is 1200r / min for 20min to obtain an electromagnetic radiation protection polymer sound insulation material. Example 6
[0084] Compared with Example 5, Example 6 is characterized in that only the damping filler prepared in Example 2 added in Example 5 is replaced by an equal amount of the damping filler prepared in Example 3, and the remaining components and preparation method of Example 6 are completely consistent with those of Example 5. Example 7
[0085] Compared with Example 5, Example 7 is that only the damping filler prepared in Example 2 added in Example 5 is replaced by the damping filler prepared in Example 4 in equal amount, and the other components and preparation method of Example 7 are exactly the same as those of Example 5.
[0086] Comparative Example 1
[0087] The preparation method of the synthetic emulsion comprises the following steps: in a nitrogen atmosphere, 64 g of deionized water, 1 g of sodium dodecylbenzene sulfonate, 1 g of nonylphenol polyoxyethylene ether, 13.2 g of styrene, 13.8 g of butyl acrylate and 6 g of methyl methacrylate are added into a reaction bottle A and dispersed evenly, stirred for 0.5-1 h, the temperature is controlled at 70°C, 0.1 g of ammonium persulfate and 0.6 g of sodium bicarbonate are added, the reaction is kept warm until blue light appears, the heat is kept warm for 1 h, 0.3 g of ammonium persulfate is added for post-elimination, ammonia water is added to adjust the pH to 8, and the synthetic emulsion is obtained by filtering.
[0088] Comparative Example 2
[0089] The preparation method of the damping filler comprises the following steps:
[0090] S1: 20g of mica powder with a particle size of 0.1um was mixed to obtain a mica component; 100mL of anhydrous ethanol and 4g of γ-methacryloxypropyltrimethoxysilane were added to a reaction kettle and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 20g of the mica component was added and dispersed evenly, the temperature was controlled at 100°C, kept warm for 0.5h, filtered and dried to obtain γ-methacryloxypropyltrimethoxysilane modified mica powder;
[0091] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0092] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0093] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0094] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0095] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min and then washed with water;
[0096] S34: Silver plating treatment: The hollow glass microbeads after sensitization treatment are placed in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) and treated at 30° C. for 40 min to obtain silver-plated hollow glass microbeads.
[0097] S35: 10 g of silver-plated hollow glass microspheres, 2.5 g of p-mercaptoaniline, and 300 mL of anhydrous ethanol were added to the reaction kettle A and dispersed evenly, and allowed to stand at room temperature for 30 h, and then washed with water and dried to obtain organic hollow glass microspheres;
[0098] S36: 10 g of organic hollow glass microspheres, 70 mL of isopropanol, and 250 mL of deionized water were added to reactor B and dispersed evenly, 3.2 g of aniline and 350 mL of 2 mol / L hydrochloric acid solution were mixed and added to the reactor, stirred at room temperature for 0.5 h, 6 g of ammonium persulfate was added, the temperature was controlled at 0°C, the reaction was kept warm for 4 h under stirring conditions, washed, filtered, and dried to obtain modified hollow glass microspheres;
[0099] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler.
[0100] Comparative Example 3
[0101] The preparation method of the damping filler comprises the following steps:
[0102] S1: 5 g of mica powder with a particle size of 38 um, 5 g of mica powder with a particle size of 75 um, 5 g of mica powder with a particle size of 19 um, and 5 g of mica powder with a particle size of 0.1 um are mixed to obtain a mica component; 100 mL of anhydrous ethanol and 4 g of γ-methacryloxypropyltrimethoxysilane are added to a reaction kettle and dispersed evenly, glacial acetic acid is added to adjust the pH to 4, 20 g of the mica component is added and dispersed evenly, the temperature is controlled at 100° C., the temperature is kept for 0.5 h, filtered, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder;
[0103] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0104] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0105] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0106] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0107] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min and then washed with water;
[0108] S34: Silver plating treatment: placing the hollow glass microbeads after sensitization treatment in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) at 30°C for 40 min to obtain silver-plated hollow glass microbeads;
[0109] S35: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of silver-plated hollow glass microspheres and 1000 mL of anhydrous ethanol were blended and added to the reactor, the temperature was controlled at 60° C., the mixture was kept warm for 2 h, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified calcium carbonate; modified hollow glass microspheres were obtained;
[0110] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler.
[0111] Comparative Example 4
[0112] The preparation method of the damping filler comprises the following steps:
[0113] S1: 5 g of mica powder with a particle size of 38 um, 5 g of mica powder with a particle size of 75 um, 5 g of mica powder with a particle size of 19 um, and 5 g of mica powder with a particle size of 0.1 um are mixed to obtain a mica component; 100 mL of anhydrous ethanol and 4 g of γ-methacryloxypropyltrimethoxysilane are added to a reaction kettle and dispersed evenly, glacial acetic acid is added to adjust the pH to 4, 20 g of the mica component is added and dispersed evenly, the temperature is controlled at 100° C., the temperature is kept for 0.5 h, filtered, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder;
[0114] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0115] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0116] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0117] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0118] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min, and then washed with water to obtain pretreated hollow glass microspheres;
[0119] S34: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of pretreated hollow glass microspheres and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60° C., the temperature was kept for 2 h, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified calcium carbonate; and organic hollow glass microspheres were obtained;
[0120] S35: Silver plating treatment: placing the organic hollow glass microspheres in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) and treating at 30°C for 40 min to obtain modified hollow glass microspheres;
[0121] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler.
[0122] Comparative Example 5
[0123] The preparation method of the damping filler comprises the following steps:
[0124] S1: 5 g of mica powder with a particle size of 38 um, 5 g of mica powder with a particle size of 75 um, 5 g of mica powder with a particle size of 19 um, and 5 g of mica powder with a particle size of 0.1 um are mixed to obtain a mica component; 100 mL of anhydrous ethanol and 4 g of γ-methacryloxypropyltrimethoxysilane are added to a reaction kettle and dispersed evenly, glacial acetic acid is added to adjust the pH to 4, 20 g of the mica component is added and dispersed evenly, the temperature is controlled at 100° C., the temperature is kept for 0.5 h, filtered, and dried to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder;
[0125] S2: 5 g of γ-methacryloxypropyltrimethoxysilane and 20 mL of anhydrous ethanol were added to a reactor and dispersed evenly, glacial acetic acid was added to adjust the pH to 4, 100 g of calcium carbonate (particle size 18 um) and 1000 mL of anhydrous ethanol were mixed and added to the reactor, the temperature was controlled at 60°C, the temperature was kept for 2 hours, filtered, washed, and dried to obtain γ-methacryloxypropyltrimethoxysilane modified calcium carbonate;
[0126] S3: The preparation method of the modified hollow glass microspheres comprises the following steps:
[0127] S31: Roughening treatment: 30 g of hollow glass microspheres (H46, average particle size 90 μm; produced by Sinosteel Ma'anshan Mining Research Institute Co., Ltd.) were placed in 6000 mL of roughening solution (60 mL / L 98 wt% sulfuric acid, 30 g / L potassium dichromate) and mechanically stirred for 10 min and then washed with water;
[0128] S32: Sensitization treatment: The roughened hollow glass microspheres were placed in a sensitization solution (20 g / L SnCl2·H2O, 10 mL / L 37 wt% HCl) and mechanically stirred for 15 min before washing with water;
[0129] S33: Activation treatment: The sensitized hollow glass microspheres were placed in an activation solution (0.1 g / L PdCl2, 1 mL / L 37 wt% HCl) and mechanically stirred for 15 min and then washed with water;
[0130] S34: 10 g of activated hollow glass microspheres, 2.5 g of p-mercaptoaniline, and 300 mL of anhydrous ethanol were added to reactor A and dispersed evenly, allowed to stand at room temperature for 30 h, washed with water, and dried to obtain component 1;
[0131] S35: 10 g of component 1, 70 mL of isopropanol and 250 mL of deionized water were added to the reactor B and dispersed evenly, 3.2 g of aniline and 350 mL of 2 mol / L hydrochloric acid solution were mixed and added to the reactor, stirred at room temperature for 0.5 h, 6 g of ammonium persulfate was added, the temperature was controlled at 0°C, the reaction was kept warm for 4 h under stirring conditions, washed, filtered and dried to obtain organic hollow glass microspheres;
[0132] S34: Silver plating treatment: The organic hollow glass microspheres were placed in a silver plating solution (10 g / L silver nitrate, 60 mL / L NH3·H20, 100 mL / L formaldehyde) and treated at 30°C for 40 min to obtain silver-plated hollow glass microspheres.
[0133] S4: 20 g of modified hollow glass microspheres, 10 g of silane-modified mica powder, and 10 g of silane-modified calcium carbonate were blended to obtain a damping filler.
[0134] Comparative Example 6
[0135] Compared with Example 5, Comparative Example 6 is characterized in that only an equal amount of the synthetic emulsion prepared in Example 1 added in Example 5 is replaced by the synthetic emulsion prepared in Comparative Example 1. The remaining components and preparation method of Comparative Example 6 are exactly the same as those of Example 5.
[0136] Comparative Example 7
[0137] Compared with Example 5, Comparative Example 7 is the case in which only the damping filler prepared in Example 2 added in Example 5 is replaced by an equal amount of the damping filler prepared in Comparative Example 2. The remaining components and preparation method of Comparative Example 7 are completely consistent with those of Example 5.
[0138] Comparative Example 8
[0139] Compared with Example 5, Comparative Example 8 is the case in which only the damping filler prepared in Example 2 added in Example 5 is replaced by an equal amount of the damping filler prepared in Comparative Example 3. The remaining components and preparation method of Comparative Example 8 are completely consistent with those of Example 5.
[0140] Comparative Example 9
[0141] Compared with Example 5, Comparative Example 9 is the case in which only the damping filler prepared in Example 2 added in Example 5 is replaced by an equal amount of the damping filler prepared in Comparative Example 4. The remaining components and preparation method of Comparative Example 9 are completely consistent with those of Example 5.
[0142] Comparative Example 10
[0143] Compared with Example 5, Comparative Example 10 is characterized in that only the damping filler prepared in Example 2 added in Example 5 is replaced by the damping filler prepared in Comparative Example 5 in equal amount, and the remaining components and preparation method of Comparative Example 10 are completely consistent with those of Example 5.
[0144] Performance Testing
[0145] (1) Loss factor: According to GB / T 18258-2000 "Test method for damping performance of damping materials", the sound insulation materials prepared in Examples 5-7 and Comparative Examples 6-10 with a size of 200×10×2.5 mm were scraped onto a damping steel bar with a size of 220 mm×10 mm×0.8 mm, and the loss factor was tested. The test results are shown in Table 1.
[0146] Table 1: Statistical table of damping performance test data of Examples 5-7 and Comparative Examples 6-10
[0147]
[0148] It can be seen from Table 1 that the sound insulation material prepared in the present application has the characteristics of large loss factor tanδ and good damping effect, and the effective damping temperature range of tanδ>0.5 is wide.
[0149] (2) Volume resistivity: The volume resistivity of the material was tested using the four-probe method in SJ 20673-1998. The test results are shown in Table 2.
[0150] (3) Electromagnetic shielding performance: According to NIM-ZY-2000-05-EMC Rules-06 Material Shielding Operation Instructions, the SE value of the shielding coating material in the electromagnetic wave frequency bands of 2.64-12.4GHz and 30-1000MHz was tested; the test results are shown in Table 2;
[0151] Table 2: Statistical table of electromagnetic shielding performance test data of Examples 5-7 and Comparative Examples 6-10
[0152]
[0153] It can be seen from Table 2 that the sound insulation material prepared in the present application has the characteristics of large loss factor tanδ and good damping effect, and the effective damping temperature range of tanδ>0.5 is wide, and it has good electromagnetic shielding performance.
[0154] (4) Adhesion: Tested according to GB / T 9286-2021 “Scratch test for paint and varnish films”. The test results are shown in Table 3.
[0155] (4) Low-temperature drop ball impact performance: After the sample is placed at (-40±2)℃ for 2h, it is quickly taken out and a 50g steel ball is dropped freely from a height of 0.5m to impact the back of the sample (the coated sample surface is the front). The test results are shown in Table 3;
[0156] Table 3: Statistical table of mechanical properties test data of Examples 5-7 and Comparative Examples 6-10
[0157]
[0158] It can be seen from Table 3 that the material prepared in this application has the characteristics of strong adhesion and good impact resistance.
[0159] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A preparation process of an electromagnetic radiation-proof polymer sound insulation material for new energy cars, characterized in that: The steps include: According to the raw material ratio, the synthetic emulsion, damping filler, dispersant, defoamer and plasticizer are evenly dispersed, and water and thickener are added to adjust the viscosity of the system to obtain an electromagnetic radiation protection polymer sound insulation material; The preparation method of the damping filler comprises the following steps: S1: Add silver-plated hollow glass microspheres, p-mercaptoaniline and anhydrous ethanol into reactor A and disperse them evenly, let them stand at room temperature for 24-36 hours, wash with water and dry them to obtain organic hollow glass microspheres; S2: adding the organic hollow glass microspheres, isopropanol and deionized water into the reaction kettle B and dispersing them evenly, blending aniline and hydrochloric acid solution and adding them into the reaction kettle, stirring at room temperature for 0.5-1h, adding ammonium persulfate, controlling the temperature at -5 to 5°C, keeping the temperature under stirring for 3-6h, washing, filtering and drying to obtain modified hollow glass microspheres; S3: blending modified hollow glass microspheres, silane-modified mica powder, and silane-modified calcium carbonate to obtain a damping filler; The preparation method of the synthetic emulsion comprises the following steps: A1: In a nitrogen atmosphere, add deionized water, emulsifier, and acrylic ester monomer into reaction bottle A and disperse evenly, stir for 0.5-1h, control the temperature at 70-90°C, add ammonium persulfate component 1 and sodium bicarbonate, keep warm until blue light appears, keep warm for 0.5-1h, add ammonium persulfate component 2 for post-elimination, adjust the pH to 8-9, filter, and obtain a water-based acrylic emulsion; A2: Add polyvinyl alcohol and aqueous acrylic emulsion into reaction bottle B and disperse them evenly to obtain a synthetic emulsion; The silane-modified mica powder is γ-methacryloxypropyltrimethoxysilane-modified mica powder; the preparation method of γ-methacryloxypropyltrimethoxysilane-modified mica powder comprises the following steps: adding anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane into a reaction kettle and dispersing them evenly, adding glacial acetic acid to adjust the pH to 4-5, adding mica components and dispersing them evenly, controlling the temperature to 100-110° C., keeping the temperature for 0.5-1h, filtering, and drying to obtain γ-methacryloxypropyltrimethoxysilane-modified mica powder; the mica component is obtained by mixing mica powders with particle sizes of 38um, 75um, 19um, and 0.1um in a mass ratio of 1:1:1:1; The silane-modified calcium carbonate is γ-methacryloxypropyltrimethoxysilane-modified calcium carbonate.
2. The preparation process of the electromagnetic radiation protection polymer sound insulation material for new energy cars according to claim 1 is characterized in that: The addition ratio of the silver-plated hollow glass microspheres, p-mercaptoaniline, and anhydrous ethanol in S1 is 10 g: 1-4 g: 100-500 mL.
3. The preparation process of the electromagnetic radiation protection polymer sound insulation material for new energy cars according to claim 1 is characterized in that: The hydrochloric acid solution in S2 is 1-2.5 mol / L hydrochloric acid solution; the addition ratio of the organic hollow glass microspheres, isopropanol, deionized water, aniline, hydrochloric acid solution, and ammonium persulfate is 10 g: 50-100 mL: 200-300 mL: 3-3.5 g: 300-400 mL: 5-8 g.
4. The preparation process of the electromagnetic radiation protection polymer sound insulation material for new energy cars according to claim 1 is characterized in that: The mass ratio of the modified hollow glass microspheres, the silane-modified mica powder and the silane-modified calcium carbonate in S3 is 15-20:10-15:
10.
5. The preparation process of the electromagnetic radiation protection polymer sound insulation material for new energy cars according to claim 1 is characterized in that: The anti-electromagnetic radiation polymer sound insulation material includes the following raw materials in weight percentage: 45-55% synthetic emulsion, 30-45% damping filler, 1-5% water, 0.3-1.5% dispersant, 0.1-0.3% defoamer, 0.1-1% plasticizer, 0.2-1% thickener, and the sum of the weight percentages of each raw material is 100%.
6. The preparation process of the electromagnetic radiation protection polymer sound insulation material for new energy cars according to claim 1 is characterized in that: In A1, the ammonium persulfate component 1 and the ammonium persulfate component 2 are both ammonium persulfate, the mass ratio of the ammonium persulfate component 1 to the ammonium persulfate component 2 is 1:2-1:3, and the ammonium persulfate accounts for 0.3-0.4% of the total mass of the aqueous acrylic emulsion; the emulsifier is obtained by mixing sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether in a mass ratio of 1:1-2; the emulsifier accounts for 2-3% of the total mass of the aqueous acrylic emulsion; the acrylic ester monomer is obtained by mixing styrene, butyl acrylate and methyl methacrylate in a mass ratio of 20-24:22-24:10, and the monomer accounts for 30-33% of the total mass of the aqueous acrylic emulsion; the sodium bicarbonate accounts for 0.5-0.8% of the total mass of the aqueous acrylic emulsion.
7. The preparation process of the electromagnetic radiation protection polymer sound insulation material for new energy cars according to claim 1 is characterized in that: The mass ratio of polyvinyl alcohol to water-based acrylic emulsion in A2 is 1:1-2.
Citation Information
Patent Citations
Water-based acrylic damping coating and preparation method thereof
CN114369400A
Automotive water-based sound insulation damping coating with high damping performance and preparation method thereof
CN115197623A